EDUCATIONAL INNOVATIONS FOR GENDER EQUALITY: USES OF TECHNOLOGY AND NEW APPROXES - Dedy Ari Nugroho; Ali Rahman; Marzuki; Rachmi Afriani; Aniati (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Currently, in Indonesia's education system, there is a gender imbalance that remains apparent. In general, Indonesian society still holds the understanding that women belong to a lower group and are lower than men, although, in the context of education, all individuals, both men and women, have the same right to education. Ironically, education, which is supposed to be a learning space for both sexes, turns out to be more sought after by men than women. This is due to the patriarchal view, that is, the view that men hold higher and more valuable positions than women. Education plays a key role in achieving gender equality in society, because through education, social norms, knowledge, and skills can be transferred. In education, women are still lagging behind men. This condition is partly due to a lack of look in society that promotes and places people to get education from women. Education that promotes gender equality is a very important strategic issue. Efforts are needed to formulate national education policies that integrate gender in a concrete way, including in gender-based curricula. As a result, women's roles and potential become limited, even when they have a desire to contribute in the field of education. To prevent inequalities in the world of education, it is important to maintain and promote gender equality in social life.